A novel rat model of vertebral inflammation–induced intervertebral disc degeneration mediated by activating cGAS/STING molecular pathway. Issue 20 (3rd September 2021) - Su, Qihang; Cai, Qiuchen; Li, Yongchao; Ge, Hengan; Zhang, Yuanzhen; Zhang, Yi; Tan, Jun; Li, Jie; Cheng, Biao; Zhang, Yan
Abstract: In this study, we describe a new rat model of vertebral inflammation–induced caudal intervertebral disc degeneration (VI‐IVDD), in which IVD structure was not damaged and controllable segment and speed degeneration was achieved. VI‐IVDD model was obtained by placing lipopolysaccharide (LPS) in the caudal vertebral bodies of rats. Rat experimental groups were set as follows: normal control group, group with a hole drilled in the middle of vertebral body and not filled with LPS (Blank group), group with a hole drilled in the middle of vertebral body and filled with LPS (Mid group), and group with hole drilled in the vertebral body in proximity of IVD and filled with LPS (NIVD group). Radiological results of VI‐IVDD rats showed a significant reduction in the intervertebral space height and decrease in MRI T2 signal intensity. Histological stainings also revealed that the more the nucleus pulposus and endplate degenerated, the more the annulus fibrosus structure appeared disorganized. Immunohistochemistry analysis demonstrated that the expression of Aggrecan and collagen‐II decreased, whereas that of MMP‐3 increased in Mid and NIVD groups. Abundant local production of pro‐inflammatory cytokines was detected together with increased infiltration of M1 macrophages in Mid and NIVD groups. Apoptosis ratio remarkably enhanced in Mid and NIVD groups. Interestingly, we found a strong activation of the cyclic GMP‐AMP synthase /stimulator of interferon gene signalling pathway, which is strictly related to inflammatory and degenerative diseases. In this study, we generated a new, reliable and reproducible IVDD rat model, in which controllable segment and speed degeneration was achieved.